Kondisi Kualitas Air di UPTD BBIAT Waiheru Kota Ambon - Leopold A Tomasila; Lolita k Tuhumena; Nancy Parera; Sara Umbekna; Lalu P. I Agamawan; Liyatin Gea; Imam Mishbach (Jurnal Akuakultur Sungai dan Danau, 2023)
The currently aquaculture have prospects that good is fish cultivation and influenced by thecnical factor and non-thecnical that determine as a requiement for cultivation business. The technical factor thar direct to influenced or failed towards cultivaation technical activity such as water quality. If there is a decrease in water quality can caused by inclusion of heavy metals to waters. The monitoring of water quality that carried out in UPTD BBIAT Waiheru only limited on physical parameters, while monitoring towards chemical parameters such as heavy metal content not done, so that not obtained an overall water quality information. For that researched needs to be done which aims to formulated direction of management water quality at UPTD BBIAT Waiheru. Ths researched by done on months October 2019 -Ferbuary 2020, at UPTD BBIAT Waiheru. Water sampling used purposive sampling and descriptive analysa. Based on the results of study incicated The parameters of Aquatic Physics at BBIAT Waiheru from January untill December are temperature average 27,200C , pH 8,54, total dissolved solids 187 mg/l, and DO 6,7 mg/l. Based on the quality standard, the temperature range at research points 1 to 7 is still within the tolerable range for the life of cultivated organisms, the pH of the water at the sampling points is still within natural limits and meets the quality standard, the TDS range at 7 sampling points is still in the range can be tolerated and the DO value obtained is still within the tolerance range and can be used to support the life of cultivated biota.